Auxiliary Companies of the Horticultural Sector as a Competitiveness Element: The Case of Almeria (Spain) - de Pablo Valenciano, Jaime (Int J Environ Res Public Health, 2019)
The horticultural model of Almeria (Spain) based on the operation of greenhouses is an international reference and has been considered as an economic miracle. Alongside this agricultural development has been the deployment of the diverse productive activity of auxiliary companies. The objective of this article is to understand how these companies operate and analyze their factors of competitiveness, competing needs, and future competitive improvements, taking as reference four of the most important subsectors (machinery, greenhouse infrastructure, plastics, and seeds). The Delphi method was used and through a panel of experts the conditioning factors of each of the variables to be analyzed (factors, needs, and competitiveness improvements) was chosen. Of the 120 companies that were sent questionnaires, 72 participated. The sectors that make up the auxiliary companies are heterogeneous and therefore the results obtained have differed among them. The synergies between the greenhouse crops and the auxiliary companies are an example of diversification of productive activity that can be extrapolated to other production areas worldwide. The future of the auxiliary companies is linked to that of the intensive agriculture and the key variables must be underscored by competitiveness and sustainability.